Posted by **NGOFAKA** on Tuesday, October 23, 2007 at 12:11pm.

if sqrt(y)=arctan(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2

- Maths -
**drwls**, Tuesday, October 23, 2007 at 12:49pm
If

sqrt(y)=arctan(x),

that means

y = [arctan(x)]^2

Let u = arctan x and use the chain rule

y = u^2

dy/dx = d(u^2)/du * du/dx

= 2 arctan(x)/(1 + x^2)

or

(1 + x^2)*dy/dx = 2 arctan x = 2 sqrt y

Are you sure you wrote

(1+x^2)dy/dx((1+x^2)dy/dx)=2 correctly?

That has (1+x^2)dy/dx appearing twice in a row. It doesnt look right

## Answer This Question

## Related Questions

- Maths - if sqrt(y)=(arctan)tan-1(x), show that (1+x^2)dy/dx((1+x^2)dy/dx)=2
- calculus - Let f be a function defined by f(x)= arctan x/2 + arctan x. the value...
- Complex numbers - For the transformation w=(z+i)/(z-i) show that as z moves ...
- Calculus - 1.Evaluate: (1/(x*sqrt(x^2-4)) I know the answer is -1/2*arctan(2/...
- precal - The values of x that are solutions to the equation cos^(2)x=sin2x in ...
- Math Help please!! - Could someone show me how to solve these problems step by ...
- Calc - Evaluate the integral (3x+4)/[(x^2+4)(3-x)]dx a. (1/2)ln(x^2+4) + ln|3-x...
- PreCalculus - I'm unsure how to even start this problem Solve for x: Arctan( -4/...
- Trigonometry - I need help with I just can't seem to get anywhere. this is as ...
- TRIGONOMETRY - Evaluate the expressions: a) arctan(-sqrt(3)) a) Arctan(-sqrt(3...

More Related Questions